CRITICAL ANALYSIS OF PAULO FREIRE'S "PEDAGOGY OF THE OPPRESSED" - Aadil Hussain Mir; Dr. R. Sivakumar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Paulo Freire's "Pedagogy of the Oppressed," first published in 1968, is a seminal work in educational theory that critiques traditional educational practices and offers a revolutionary framework for learning. Freire challenges the "banking model" of education, where students are passive recipients of knowledge, advocating instead for a "problem-posing" model that emphasizes dialogue, critical thinking, and active engagement. Central to Freire’s pedagogy is the concept of critical consciousness, or conscientização, which involves developing an awareness of social, political, and economic forces that shape one’s life. Freire argues that education should be a collaborative process that empowers students to question and transform oppressive structures in their society. By fostering a more participatory and democratic learning environment, Freire’s approach aims to liberate both students and educators from traditional hierarchies and promote social justice. "Pedagogy of the Oppressed" has significantly influenced educational practices and social movements worldwide, emphasizing the role of education in achieving personal and collective emancipation. Despite criticisms regarding its feasibility and implementation, Freire’s work remains a foundational text in critical pedagogy, providing valuable insights into the potential of education as a transformative tool for societal change.